Literasi Digital Berbasis Kaganga Mobile Pada Guru Bahasa Lampung - Masitoh; Prihatmojo, Agung (Universitas Muhammadiyah Malang, 2022)
Online learning makes it difficult for teachers to use appropriate learning media for local content subjects in the Lampung language. Training on the use of the Kaganga mobile application as an e-learning medium is expected to be a solution for online learning in Lampung Language. Kaganga mobile is an android application that has quite complete features, namely learning Lampung language, letters, punctuation marks, numbers, and examples of words, both writing and pronunciation. The kaganga mobile application is suitable for use in online learning of Lampung language and literature subjects in elementary schools. Kaganga mobile is an innovation and creation that can be used by Lampung language teachers so that students are interested in learning Lampung language in online learning. To be able to apply kaganga mobile, digital literacy skills are needed for every teacher. This activity is carried out in the form of Community Service. This community service partnered with the North Lampung Education and Culture Office with a focus on participants, namely Lampung language teachers, elementary schools throughout North Lampung. In community service activities as many as 70 Lampung Language Teachers will receive training and assistance for digital literacy skills based on mobile kaganga in learning the Lampung language.